Composite cathode material, preparation method thereof, cathode sheet and battery
By coating the surface of ternary materials with bamboo-based carbon materials containing aromatic groups, a core-shell structured composite cathode material is formed, which solves the problems of low electronic conductivity and poor structural stability of ternary materials in lithium-ion batteries, and improves the cycle stability and charge-discharge efficiency of the battery.
Patent Information
- Application Number
- CN202510653373.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-20
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2045-05-20
AI Technical Summary
Existing ternary materials have low electronic conductivity, limited lithium-ion diffusion rate, and poor structural stability in lithium-ion batteries, which affects their application in high-power and long-cycle-life batteries.
A core-shell structured composite cathode material is used, in which the core is a ternary material and the shell is a bamboo-based carbon material containing aromatic groups. By coating the surface of the ternary material with bamboo-based carbon material, a stable coating structure is formed, which improves electronic conductivity and ion diffusion rate.
It improves the cycle stability and charge/discharge efficiency of the battery, increases the contact area between the electrolyte and the material, promotes the transport and diffusion of active ions, reduces the internal resistance of the battery, and improves the charge/discharge performance of the battery.
Smart Images

Figure CN120709309B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and more specifically, to a composite cathode material, its preparation method, cathode sheet, and battery. Background Technology
[0002] Ternary materials (such as high-nickel ternary cathode materials) are important cathode materials for lithium-ion batteries, possessing advantages such as high specific capacity, good cycle stability, and relatively low cost, and have broad application prospects in modern energy storage. However, current ternary materials still face some challenges in practical applications, such as low electronic conductivity, limited lithium-ion diffusion rate, and changes in lattice parameters during charge-discharge cycles, leading to volume changes and poor structural stability. These problems limit their application in high-power, long-cycle-life lithium-ion batteries.
[0003] To improve the performance of ternary materials (such as high-nickel ternary cathode materials), various modification methods have been employed, including elemental doping and surface coating. However, these methods still have some limitations in practical applications. For example, elemental doping may alter the crystal structure of the material, leading to performance instability. Among these methods, carbon coating technology, as an effective surface modification technique, has attracted widespread attention. By coating the surface of ternary materials with a layer of carbon, the conductivity of the material can be improved, charge transport efficiency can be enhanced, structural stability can be strengthened, and side reactions can be suppressed. However, traditional carbon-coated materials mostly use amorphous carbon or graphitized carbon, whose structures and properties are relatively simple, limiting their ability to improve the overall performance of ternary materials.
[0004] Therefore, developing a simple, efficient, and low-cost method for modifying ternary cathode materials, as well as the resulting modified cathode materials, is of significant practical importance. Summary of the Invention
[0005] In view of this, the present invention aims to at least partially solve one of the technical problems in the related art. To this end, the present invention provides a composite cathode material and its preparation method, a cathode sheet, and a battery. This composite cathode material possesses high electronic conductivity, ion diffusion rate, and structural stability, which can improve its performance in batteries such as lithium-ion batteries, for example, by enhancing the battery's cycle stability.
[0006] To solve the above-mentioned technical problems, the present invention is implemented as follows:
[0007] According to a first aspect of the present invention, an embodiment of the present invention provides a composite cathode material having a core-shell structure, including a core and a shell; wherein the core comprises a ternary material, the shell covers at least a portion of the core, and the shell comprises a bamboo-based carbon material; the bamboo-based carbon material contains aromatic groups.
[0008] In addition, the composite cathode material according to the present invention may also have the following additional technical features:
[0009] In some embodiments, the aromatic groups have a mass content of 12%-16% based on the mass of the bamboo-based carbon material.
[0010] In some embodiments, the aromatic group includes a phenyl group.
[0011] In some embodiments, the bamboo-based carbon material also contains hydroxyl and / or quinone groups.
[0012] In some embodiments, the hydroxyl content is 8%-12% based on the total mass of aromatic groups.
[0013] In some embodiments, the quinone group content is 10%-15% based on the total mass of aromatic groups.
[0014] In some embodiments, the composite cathode material satisfies at least one of the following characteristics: (1) the porosity of the composite cathode material is 60%-80%; (2) the specific surface area of the composite cathode material is 200-1000 m². 2 / g, preferably 700-950m 2 / g; (3) The conductivity of the composite cathode material is 10-100S / cm, preferably 90-100S / cm; (4) The average particle size of the composite cathode material is 150nm-300nm; (5) The average particle size of the core is 130nm-200nm; (6) The average thickness of the shell is 10nm-50nm; (7) The ternary material includes nickel-based ternary material.
[0015] In some embodiments, the nickel-based ternary material includes nickel-cobalt-manganese ternary cathode active material and / or nickel-cobalt-aluminum ternary cathode active material.
[0016] In some embodiments, the ternary material includes a high-nickel ternary material.
[0017] According to a second aspect of the present invention, embodiments of the present invention provide a method for preparing a composite cathode material, the method comprising:
[0018] S1. Bamboo-based precursors are carbonized in the presence of a mixture of reducing gas and oxygen and ester compounds to obtain bamboo-based carbon.
[0019] S2. The bamboo-based carbon and ternary material are mixed in the presence of a solvent, and then dried and carbonized to obtain the composite cathode material.
[0020] The composite cathode material has a core-shell structure, including a core and a shell. The core contains a ternary material, and the shell covers at least a portion of the core. The shell includes a bamboo-based carbon material containing aromatic groups.
[0021] In some of these embodiments, the carbonization temperature in step S1 and the carbonization coating temperature in step S2 are each independently 200-400°C.
[0022] In some of these embodiments, the carbonization temperature in step S1 is lower than the carbonization coating temperature in step S2.
[0023] In some embodiments, the temperature difference between carbonization in step S1 and carbonization coating in step S2 is 30-100°C.
[0024] In some embodiments, the carbonization conditions in step S1 include: a pressure of 0.05-0.2 MPa, a temperature of 200-350°C, and a time of 2-5 hours.
[0025] In some embodiments, the carbonization coating conditions in step S2 include: a temperature of 250-400°C and a time of 3-6 hours.
[0026] There are no special restrictions on the mixing in step S2 of this invention. As long as the materials can be mixed evenly, it is generally sufficient to mix and stir for 2-5 hours.
[0027] According to the present invention, it is understood that the drying in step S2 of the present invention is to dry the solid material after mixing and stirring, that is, to dry it after filtration. The drying method can be a conventional method in the art, and the present invention will not elaborate on it here.
[0028] In some embodiments, the ester compound includes at least one of phosphate esters, borate esters, and carboxylic esters, preferably including phosphate esters.
[0029] In some embodiments, the phosphate ester includes at least one of trimethyl phosphate, triethyl phosphate, and tripropyl phosphate.
[0030] In some of these embodiments, the phosphate ester includes trimethyl phosphate.
[0031] In some embodiments, the volume ratio of reducing gas to oxygen in the mixed gas is 1.5-4:1.
[0032] In some of these embodiments, the reducing gas includes hydrogen.
[0033] In some of these embodiments, the ternary material includes a nickel-based ternary material.
[0034] In some embodiments, the nickel-based ternary material includes nickel-cobalt-manganese ternary cathode active material and / or nickel-cobalt-aluminum ternary cathode active material; preferably, the ternary material includes a high-nickel ternary material.
[0035] In some embodiments, the bamboo-based precursor is derived from at least one of moso bamboo, bitter bamboo, ci bamboo and kang bamboo, and in some preferred cases the bamboo-based precursor is derived from moso bamboo.
[0036] In some of these embodiments, the solvent includes alcohol solvents.
[0037] In some embodiments, the alcohol solvent includes at least one of methanol, ethanol, or ethylene glycol.
[0038] In some embodiments, in step S1, the mass ratio of the phosphate ester to the bamboo-based precursor is 1:0.8-2.5.
[0039] In some embodiments, in step S2, the mass of the bamboo-based carbon is 1%-15% of the mass of the ternary material.
[0040] According to a third aspect of the present invention, an embodiment of the present invention provides a positive electrode sheet comprising a current collector, wherein a first active material layer is provided on at least one side of the current collector, and a second active material layer is provided on the surface of the first active material layer away from the current collector, wherein the first active material layer and the second active material layer each independently contain the composite positive electrode material described in the first aspect of the present invention or the composite positive electrode material prepared by the preparation method described in the second aspect of the present invention.
[0041] In some of these embodiments, the average thickness of the outer shell of the composite positive electrode material in the first active material layer is denoted as T1, and the average thickness of the outer shell of the composite positive electrode material in the second active material layer is denoted as T2. T1 and T2 satisfy the condition that T1 is greater than T2.
[0042] In some embodiments, the numerical difference between T1 and T2 is 5nm-40nm, preferably 10nm-30nm.
[0043] In some of these implementations, the value of T1 is 15nm-50nm.
[0044] In some of these implementations, the value of T2 is 10nm-30nm.
[0045] In some embodiments, the thickness of the first active material layer and the thickness of the second active material layer are each independently 100 μm-150 μm.
[0046] In some embodiments, the first active material layer and the second active material layer each independently contain a conductive agent and a binder.
[0047] In some embodiments, the mass content of the composite cathode material in the first active material layer and the second active material layer is independently greater than 80%.
[0048] According to a fourth aspect of the present invention, an embodiment of the present invention provides a battery comprising a negative electrode and a positive electrode as described in the third aspect of the present invention.
[0049] Implementing the technical solution of the present invention has at least the following beneficial effects:
[0050] The composite cathode material of this invention has a core-shell structure, and the outer shell comprises bamboo-based carbon material containing aromatic groups. Thus, by coating the surface of the ternary material core with bamboo-based carbon material, the large specific surface area and high porosity of bamboo-based carbon material provide more contact sites for the interaction between the bamboo-based carbon material and the ternary material. This not only helps the bamboo-based carbon material to more uniformly coat the surface of the ternary material particles, forming a more stable coating structure, but also increases the contact area between the electrolyte and the composite cathode material during battery charging and discharging, promoting the transport and diffusion of active ions such as lithium ions, and further improving the electrochemical performance of the material. Furthermore, the coating modification using bamboo-based carbon material can introduce components with good conductivity into the material surface, effectively improving electronic conductivity, reducing battery internal resistance, and enhancing charge / discharge efficiency and rate performance. Furthermore, the bamboo-based carbon material in this invention contains aromatic groups. The presence of these aromatic groups provides a basis for the orderly growth of carbon structures, helps to form bamboo-based carbon with abundant pores and a reasonable pore size distribution, increases the specific surface area of bamboo carbon, and thus provides more contact sites for interaction with ternary materials. This is more conducive to the contact between the electrolyte and the material, promotes the adsorption and diffusion of ions, and improves the charge and discharge performance of the battery. It also helps to improve the stability of the battery during cycling.
[0051] Therefore, the composite cathode material of the present invention has high electronic conductivity, which can promote the diffusion rate and structural stability of active ions in the battery, thereby improving its performance in ion batteries, such as improving the cycle performance of the battery.
[0052] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description
[0053] Figure 1The image shown is a SEM image of the composite cathode material A1 provided in Embodiment 1 of the present invention;
[0054] Figure 2 The image shown is an infrared spectrum of the bamboo-based carbon material shell of the composite cathode material A1 provided in Embodiment 1 of the present invention;
[0055] Figure 3 The image shown is an infrared spectrum of the bamboo-based carbon material shell of the composite cathode material D1 provided in Embodiment 4 of the present invention. Detailed Implementation
[0056] The present application will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.
[0057] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0058] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0059] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0060] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0061] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0062] Unless otherwise specified, room temperature in this application refers to 10-30°C.
[0063] To improve the performance of ternary materials, carbon coating can be used. However, conventional carbon coating materials are mostly amorphous carbon or graphitized carbon, with relatively simple structures and properties, which limits their ability to improve the overall performance of ternary materials. Therefore, to alleviate these problems, the inventors of this invention discovered that bamboo-based carbon materials can interact better with ternary materials, providing more contact sites and resulting in better electrochemical performance of the composite cathode material. The following is a detailed description of this application.
[0064] In some embodiments, the present invention provides a composite cathode material having a core-shell structure, the composite cathode material having a core-shell structure including a core and a shell; wherein the core comprises a ternary material, the shell covers at least a portion of the core, and the shell comprises a bamboo-based carbon material; the bamboo-based carbon material contains aromatic groups.
[0065] In this core-shell structured composite cathode material, the outer shell covers or encapsulates at least a portion of the core, which can protect or improve the core, thereby enhancing the structural stability of the composite cathode material and optimizing its electrochemical performance. The outer shell forming on at least a portion of the core's surface means that the shell can completely encapsulate the core, or it can cover only a portion of the core's outer surface; that is, the shell can completely encapsulate the core or only cover a portion of the core's surface, preferably completely encapsulating it, which is more conducive to improving the structural stability and electrochemical performance of the composite cathode material.
[0066] The provided composite cathode material has a core-shell structure, where the core can be a traditional ternary material, and the shell includes bamboo-based carbon material. This bamboo-based carbon material mainly refers to carbon materials derived from bamboo as a precursor. Furthermore, unlike traditional carbon materials, the bamboo-based carbon material in this application also contains aromatic groups, which is more conducive to improving the relevant electrochemical performance of the composite cathode material. Specifically:
[0067] The composite cathode material of this invention exhibits high electronic conductivity and enhances battery cycle stability. The main reasons for this are as follows: Firstly, the aromatic groups in the bamboo-based carbon material can interact through π-π stacking and other means to form a stable coating layer on the surface of the ternary material core. This coating layer can buffer the volume change stress during cycling, suppressing the aggregation and cracking of core particles. In other words, the outer shell containing bamboo-based carbon material covers the core surface, resulting in a more stable coating structure. Therefore, by coating the surface of the ternary material with bamboo-based carbon material containing aromatic groups, the problem of decreased material structural stability caused by changes in the crystal structure due to repeated insertion and extraction of active ions (such as lithium ions) during cycling can be alleviated. On the other hand, the aromatic groups in bamboo-based carbon materials possess a conjugated π-electron system. This structure allows electrons to move relatively freely within the molecule, endowing bamboo-based carbon with good intrinsic conductivity. When the outer shell of bamboo-based carbon material coats the surface of the core containing ternary material, the conductive network formed by the aromatic groups can effectively reduce the charge transfer resistance of the material. During battery charging and discharging, electrons can be transported more smoothly between the electrode material and the electrolyte, thereby significantly improving the rate performance of the ternary electrode material. For example, during high current density charging and discharging, composite cathode materials with an aromatic group conductive network can maintain a higher capacity. Compared with materials without aromatic groups, the capacity retention rate can be increased by 10%-20%. At the same time, during battery charging and discharging, it can increase the contact area between the electrolyte and the electrode material, promote the transport and diffusion of active ions (such as lithium ions), and further improve the electrochemical performance of the material.
[0068] Furthermore, the inventors of this invention discovered during battery charging and discharging that the electrolyte undergoes side reactions with the surface of the ternary material, generating a harmful interfacial film that affects battery performance. The aromatic groups on the surface of the bamboo-based carbon material in this invention possess certain chemical activity, enabling them to react with lithium hexafluorophosphate and organic solvents such as EC and DMC in the electrolyte, forming a more stable and dense solid electrolyte interphase (SEI) film on the surface of the ternary material. This SEI film can prevent further side reactions between the electrolyte and the interior of the NCM material, reducing the consumption of active lithium and improving the battery's coulombic efficiency.
[0069] Furthermore, compared to conventional carbon coating materials, which are mostly amorphous carbon or graphitized carbon, using bamboo-based carbon materials for coating can increase the specific surface area and porosity. This is mainly because bamboo-based carbon, due to its unique low-temperature carbonization process, possesses a rich porous structure. The fibrous structure of bamboo itself forms a large number of micropores and mesopores during carbonization. Testing shows that the porosity of bamboo-based carbon can reach 60%-80%, while the porosity of conventional carbon coating materials is often below 40%. Higher porosity translates to a larger specific surface area; the specific surface area of bamboo-based carbon materials is generally 200-500 m². 2 Between / g, while conventional carbon-coated materials are mostly between 100m 2 The high porosity and large specific surface area of bamboo-based carbon provide more contact sites for the interaction between the carbon and the positive electrode active material. This not only helps the bamboo-based carbon to coat the surface of the positive electrode particles more uniformly, forming a more stable coating structure, but also increases the contact area between the electrolyte and the electrode material during battery charging and discharging, promoting the transport and diffusion of active ions (such as lithium ions) and further improving the electrochemical performance of the material.
[0070] This application introduces a component with good electrical conductivity into the surface of a ternary material by coating it with bamboo-based carbon material, which can effectively improve electronic conductivity, reduce battery internal resistance, and thus improve charge / discharge efficiency and rate performance.
[0071] In a preferred embodiment of this application, the formed composite cathode material is a nanoscale material. Therefore, the formed nanocomposite material increases the specific surface area, providing more diffusion channels for active ions such as lithium ions, shortening the diffusion path, and accelerating the diffusion rate. This, in turn, accelerates the diffusion of active ions (e.g., lithium ions), thereby improving the battery's charge and discharge performance.
[0072] According to the present invention, in some embodiments, based on the mass of the bamboo-based carbon material, the mass content of aromatic groups is 12%-16%, for example, 12%, 13%, 14%, 15%, 16%, or any combination of two of the above values.
[0073] In this invention, controlling the content of aromatic groups within the above-mentioned range can better improve the conductivity and stability of the composite cathode material, and the composite cathode material can better improve the coulombic efficiency of the battery.
[0074] According to the present invention, the aromatic groups in the bamboo-based carbon material include benzene ring structures that, through chemical reactions (e.g., covalent bonding or group condensation), construct the carbon skeleton structure of the bamboo-based carbon. In some embodiments, the aromatic groups include phenyl groups.
[0075] According to the present invention, in some embodiments, the bamboo-based carbon material further contains hydroxyl and / or quinone groups.
[0076] In this invention, hydroxyl and quinone groups can be attached to aromatic groups or to other chemical chains within the shell, preferably to aromatic groups. That is, in the bamboo-based carbon material of this application, the aromatic groups may include phenyl groups, and the aromatic groups may also include phenyl groups with one or both hydroxyl and quinone groups attached to them. Alternatively, the bamboo-based carbon material of this application may include aromatic groups, and groups with one or both hydroxyl and quinone groups attached to them; wherein the aromatic groups include phenyl groups. Preferably, the aromatic groups include groups with one or both hydroxyl and quinone groups attached to them, as well as phenyl groups. More preferably, the aromatic groups include groups with hydroxyl and quinone groups attached to them, as well as phenyl groups.
[0077] When the bamboo-based carbon material of the present invention contains one or both of hydroxyl and quinone groups, it is beneficial to the contact between the composite cathode material and the electrolyte, promotes the adsorption and diffusion of ions, and improves the charge and discharge performance of the battery. In particular, the presence of quinone groups enables the formation of chemical bonds or strong interactions between the shell material and the core, enhances the interfacial bonding force between the two, makes the structure of the composite material more stable, helps to maintain structural integrity during charge and discharge, and improves the cycle performance of the battery.
[0078] The functional groups in the bamboo-based carbon material of this invention can be determined by conventional methods in the art, such as infrared spectroscopy, and there is no limitation on this.
[0079] According to the present invention, in some embodiments, the mass content of hydroxyl groups is 8%-12% based on the total mass of aromatic groups, for example, 8%, 9%, 10%, 11%, 12%, or any combination of two of the above values.
[0080] In this invention, by controlling the content of hydroxyl groups within the above-mentioned range, the composite cathode material can better promote the adsorption and diffusion of active ions (such as lithium ions) when in contact with the electrolyte, thereby improving the charge and discharge performance of the battery.
[0081] According to the present invention, in some embodiments, the mass content of quinone groups is 10%-15% based on the total mass of aromatic groups, for example, 10%, 11%, 12%, 13%, 14%, 15%, or any combination of two of the above values.
[0082] In this invention, by controlling the content of quinone groups within the above-mentioned range, the composite cathode material exhibits superior structural stability and electrochemical performance, thereby better improving the cycle performance of the battery.
[0083] In this invention, the contents of aromatic groups, hydroxyl groups, and quinone groups can be determined by gas chromatography-mass spectrometry (GC-MS). For example, the content of aromatic groups can be determined by the following method:
[0084] Gas chromatography conditions: A polar DB-5MS column was used; high-purity helium was used as the carrier gas, and the flow rate was controlled at 1-2 mL / min; the injection port temperature was set to 250-300℃; a split injection method was used, with a split ratio of 10:1-50:1; the temperature program conditions were: an initial temperature of 50-80℃, held for 1-2 minutes, and then increased to 250-300℃ at a rate of 5-10℃ / min and held for 5-10 minutes to ensure that aromatic hydrocarbons with different boiling points could be fully separated.
[0085] Quantitative analysis: A series of standard solutions with concentrations ranging from 0.1 to 10 mg / L were prepared using toluene. These standard solutions were injected into a GC-MS instrument to obtain chromatograms of each standard. Then, the shell of the treated composite cathode material was injected into the instrument, and the curve overlapping with the curves of the previous series of standard solutions was selected to determine the content of aromatic hydrocarbons in the bamboo-based carbon sample.
[0086] In addition, the contents of hydroxyl and quinone groups can also be determined by conventional gas chromatography-mass spectrometry (GC-MS), which will not be elaborated upon in this invention.
[0087] According to the present invention, those skilled in the art will understand that the bamboo-based carbon material of the present invention refers to a material formed by bamboo through a carbonization process. During the carbonization process, the fibrous structure of bamboo itself forms a large number of micropores and mesopores. In some embodiments, the porosity of the composite cathode material is 60%-80%, for example, 60%, 62%, 65%, 68%, 70%, 72.5%, 75%, 76.5%, 78%, 80%, or any range of two of the above values.
[0088] The porosity of the composite cathode material in this invention can be determined by methods such as BET and mercury porosimetry.
[0089] According to the present invention, higher porosity implies a larger specific surface area; in some embodiments, the specific surface area of the composite cathode material is 200-1000 m². 2 / g, for example, 200m 2 / g、300m 2 / g、400m 2 / g、500m 2 / g、600m 2 / g、650m 2 / g、710m 2 / g、755m 2 / g、800m 2 / g、850m2 / g、900m 2 / g、925m 2 / g、950m 2 / g, 1000m 2 / g, or a range of any two of the above values, preferably 700-950m 2 / g.
[0090] The specific surface area of the composite cathode material in this invention can be determined by the conventional physical adsorption BET method in the art.
[0091] The composite cathode material in this invention possesses high porosity and a large specific surface area, providing more contact sites for the interaction between bamboo-based carbon and the cathode active material. More importantly, the outer shell and core can form a more stable core-shell structure; and during battery charging and discharging, it can increase the contact area between the electrolyte and the composite cathode material, promoting the transport and diffusion of active ions (such as lithium ions), and further improving the electrochemical performance of the material.
[0092] According to the present invention, the outer shell contains bamboo-based carbon material, and the bamboo-based carbon material contains aromatic groups, which make the outer shell material have good electrical conductivity, effectively improving electronic conductivity, reducing battery internal resistance, and improving charge-discharge efficiency and rate performance. In some embodiments, the conductivity of the composite positive electrode material is 10-100 S / cm, for example, 10 S / cm, 20 S / cm, 30 S / cm, 40 S / cm, 50 S / cm, 60 S / cm, 65 S / cm, 69 S / cm, 70 S / cm, 75 S / cm, 80 S / cm, 90 S / cm, 92 S / cm, 95 S / cm, 96 S / cm, 97 S / cm, 100 S / cm, or any two of the above values, preferably 90-100 S / cm.
[0093] According to the present invention, the size of the composite cathode material can be selected within a wide range as long as the purpose of the present invention can be achieved. In some embodiments, the average particle size of the composite cathode material is 150nm-300nm.
[0094] According to the present invention, the size of the core can be selected within a wide range as long as the purpose of the invention is achieved. In some embodiments, the average particle size of the core is 130 nm-200 nm. The advantages of the present invention are illustrated in the following embodiments using a core material with an average particle size of 150 nm as an example, but this does not represent a limitation of the invention.
[0095] According to the present invention, the thickness of the outer shell can be selected within a wide range as long as the purpose of the present invention can be achieved. In some embodiments, the average thickness of the outer shell is 10nm-50nm, for example, 10nm, 17.5nm, 20nm, 25nm, 27.5nm, 30nm, 35nm, 40nm, 42.5nm, 45nm, 50nm, or any two of the above values.
[0096] In this invention, the average thickness of the outer shell can be obtained by transmission electron microscopy. Specifically, a curve can be drawn at the outer edge of the entire core. The distance between this curve and the outer edge of the entire composite cathode material is the thickness of the composite cathode material shell. The average value of twenty randomly selected positions is the average thickness of the shell. The sum of twice the average thickness and the average particle size of the core is the average particle size of the composite cathode material.
[0097] According to the present invention, ternary materials refer to ternary cathode materials composed of three metals (e.g., transition metals), including nickel-based ternary materials.
[0098] According to the present invention, nickel-based ternary materials refer to ternary cathode materials containing nickel metal. In some embodiments, nickel-based ternary materials include nickel-cobalt-manganese ternary cathode active materials (NCM, LiNi). x Co y Mn z O2, where x > 0, y > 0, z > 0) and / or nickel-cobalt-aluminum ternary cathode active material (NCA, LiNi) x Co y Al z O2, where x > 0, y > 0, z > 0). Nickel-cobalt-manganese ternary cathode active materials have high theoretical specific capacity, typically between 150-280 mAh / g. A high theoretical specific capacity means that more electrical energy can be stored in battery applications, thus providing longer driving range for electronic devices, electric vehicles, etc. This invention uses nickel-cobalt-manganese ternary cathode active materials as an example to illustrate the advantages of the invention, but this does not constitute a limitation on the invention.
[0099] Optionally, when the parameters of Ni, Co, and Mn are within the range of 0.4≤x≤0.8, 0.1≤y≤0.3, 0.1≤z≤0.3, and x+y+z=1, LiNi is included. x Co y Mn zThe O2 core exhibits superior performance during composite modification with bamboo-based carbon materials. Within this ratio range, the material's crystal structure is relatively stable, Ni provides high specific capacity, Co enhances electronic conductivity and structural stability, and Mn contributes to improved safety and cycle life. Examples of NCM series materials used in this invention include NCM111 (Ni:Co:Mn = 1:1:1), NCM523, NCM622, and NCM811. Preferably, the NCM is selected from NCM811. While NCM523 or NCM811 are used as examples to illustrate the advantages of this invention, they do not represent limitations on the invention.
[0100] In this invention, the ternary material is preferably a high-nickel ternary material, such as NCM811, which has advantages such as high specific capacity, good cycle stability and relatively low cost.
[0101] According to the present invention, as long as the purpose of the present invention can be achieved, the preparation method of the composite cathode material in the present invention is not particularly limited. For example, bamboo-based precursor is carbonized to obtain bamboo-based carbon, and then carbonized and coated with ternary material. Preferably, in some embodiments, the composite cathode material can be prepared according to the preparation method provided below.
[0102] According to the present invention, those skilled in the art should understand that all the features and effects of the above-mentioned "positive electrode composite material" of the present invention are also applicable to the "preparation method of the composite positive electrode material provided below", and the present invention will not elaborate on them further.
[0103] According to another aspect of the present invention, a method for preparing a composite cathode material is provided, the method comprising:
[0104] S1. Bamboo-based precursors are carbonized in the presence of a mixture of reducing gas and oxygen and ester compounds to obtain bamboo-based carbon.
[0105] S2. The bamboo-based carbon and ternary material are mixed in the presence of a solvent, and then dried and carbonized to obtain the composite cathode material.
[0106] The composite cathode material has a core-shell structure, including a core and a shell. The core contains a ternary material, and the shell covers at least a portion of the core. The shell includes a bamboo-based carbon material containing aromatic groups.
[0107] The method for preparing the composite cathode material in this invention is simple and easy to implement. Bamboo is widely available and inexpensive, and it has good economic and environmental benefits, making it suitable for large-scale industrial production.
[0108] In the preparation method of the composite cathode material of the present invention, a bamboo-based carbon material containing aromatic groups is first prepared. Further, during low-temperature carbonization, the aromatic groups in bamboo act as active sites for pyrolysis reactions, initiating a series of condensation and aromatization reactions. As the temperature increases, the lignin in the bamboo undergoes pyrolysis. During the carbonization process (e.g., in the low-temperature carbonization range of 200-350℃), aromatic groups gradually form and stabilize, their benzene ring structures interconnecting and condensing to gradually construct the carbon skeleton structure of the bamboo-based carbon. The presence of these aromatic groups provides a foundation for the orderly growth of the carbon structure, helping to form a bamboo-based carbon material with abundant pores and a reasonable pore size distribution, increasing the specific surface area of the bamboo-based carbon material, and providing more contact sites for subsequent interaction with ternary materials. Specifically, the carbonyl and phenolic hydroxyl groups in the bamboo-based carbon are reduced and oxidized to hydroxyl and quinone groups in a hydrogen-oxygen mixed gas atmosphere. The reduced hydroxyl groups can increase the active sites on the material surface, facilitating contact between the electrolyte and the material, promoting ion adsorption and diffusion, and improving the charge-discharge performance of the battery. This helps to improve the stability of the battery during cycling. The formation of quinone groups can form chemical bonds or strong interactions between bamboo-based carbon materials and ternary materials, enhancing the interfacial bonding force between the two, making the composite material structure more stable, which is beneficial to maintaining structural integrity during charging and discharging and improving the cycle performance of the battery.
[0109] According to the present invention, in some embodiments, the carbonization temperature in step S1 and the carbonization coating temperature in step S2 are each independently 200-400°C. That is, in step S1, the carbonization temperature of the bamboo-based precursor is 200-400°C; in step S2, the carbonization coating temperature after mixing the bamboo-based carbon and the ternary material is 200-400°C. The carbonization temperature in step S1 and the carbonization coating temperature in step S2 can be the same or different.
[0110] In this invention, by controlling the carbonization temperature in step S1 and the carbonization coating temperature in step S2 within the above-mentioned range, which is within the low-temperature carbonization range, the small molecule organic matter generated by cellulose pyrolysis can undergo condensation and aromatization reactions more efficiently, which helps to form an ordered pore structure and high-quality bamboo-based carbon material. This makes the prepared composite cathode material more conducive to contact with the electrolyte and promotes the transport of active ions (such as lithium ions).
[0111] According to the present invention, in some embodiments, the carbonization temperature in step S1 is lower than the carbonization coating temperature in step S2.
[0112] In this invention, controlling the carbonization temperature in step S1 to be lower than the carbonization coating temperature in step S2 results in a composite cathode material with superior electrochemical performance.
[0113] According to the present invention, in some embodiments, the temperature difference between carbonization in step S1 and carbonization coating in step S2 is 30-100°C, for example, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, or any range of two of the above values.
[0114] According to the present invention, in some embodiments, the carbonization conditions in step S1 include: a pressure of 0.05-0.2 MPa, for example 0.05 MPa, 0.1 MPa, 0.15 MPa, 0.2 MPa, or any range of two of the above values.
[0115] In this invention, the pressure in step S1 is related to the content of the mixture containing reducing gas and oxygen during carbonization.
[0116] According to the present invention, in some embodiments, the carbonization conditions in step S1 include: a temperature of 200-350°C, for example 200°C, 230°C, 250°C, 275°C, 300°C, or any range of two of the above values.
[0117] According to the present invention, those skilled in the art can raise the temperature to the carbonization temperature in step S1 at a certain heating rate according to the required carbonization temperature, for example, at a heating rate of 0.5-10℃ / min, preferably 1-5℃ / min, to the carbonization temperature in step S1.
[0118] In this invention, controlling the carbonization temperature in step S1 within the above-mentioned range can construct a more stable carbon skeleton structure of bamboo-based carbon material, which is beneficial for subsequent interaction with ternary materials, providing more contact sites and helping to improve the stability of the battery during cycling.
[0119] According to the present invention, the carbonization time in step S1 can be adjusted according to the carbonization temperature. In some embodiments, the carbonization conditions in step S1 include: a time of 3-6 hours, for example, 3 hours, 3.25 hours, 3.5 hours, 3.58 hours, 3.6 hours, 3.8 hours, 4 hours, 4.2 hours, 4.5 hours, 5 hours, or any range of two of the above values.
[0120] According to some embodiments of the present invention, in step S2, the conditions for carbonization coating include: a temperature of 250-400°C, for example, 250°C, 275°C, 300°C, 325°C, 350°C, 375°C, 400°C, or a range of any two of the above values.
[0121] In this invention, controlling the carbonization coating temperature in step S2 within the above-mentioned range can provide more contact sites for the bamboo-based carbon material to better interact with the ternary material, and can form a more stable coating structure.
[0122] According to the present invention, the carbon coating conditions in step S2 can be adjusted according to the stability of the corresponding carbon coating. In some embodiments, the carbonization coating conditions include: a time of 3-6 hours, for example, 3 hours, 3.25 hours, 3.5 hours, 3.75 hours, 4 hours, 4.25 hours, 4.5 hours, 4.75 hours, 5 hours, 6 hours, or any range of two of the above values.
[0123] According to the present invention, ester compounds refer to compounds formed by esterification reaction of inorganic acids (such as sulfuric acid, nitric acid, phosphoric acid, etc.) or organic acids with alcohols (or phenols). In some embodiments, the ester compounds include at least one of phosphate esters, borate esters and carboxylic esters.
[0124] In this invention, ester compounds are used as protective agents during the carbonization process, which helps to guide the directional arrangement and condensation reaction of pyrolysis products and promotes the orderly growth of aromatic structures.
[0125] According to the present invention, phosphate ester refers to a compound formed by the reaction of phosphoric acid and alcohol. In some embodiments, phosphate ester includes at least one of trimethyl phosphate, triethyl phosphate and tripropyl phosphate, preferably trimethyl phosphate.
[0126] According to the present invention, borate esters refer to compounds formed by the reaction of boric acid and alcohol, and examples of borate esters include trimethyl borate, triethyl borate, triphenyl borate, etc.
[0127] According to the present invention, a carboxylic acid ester refers to a compound formed by the reaction of a compound containing a carboxylic acid with an alcohol. Examples of carboxylic acid esters include dimethyl phthalate and diethyl phthalate.
[0128] According to the present invention, in some embodiments, the ester compounds include phosphate esters.
[0129] Through in-depth research, the inventors of this invention discovered that when phosphate esters, such as trimethyl phosphate, are used as protective agents in the carbonization process, the resulting composite cathode material exhibits better electrochemical performance. This is because phosphorus atoms in the molecule can interact with the aromatic structures in bamboo. This interaction helps guide the directional arrangement and condensation reaction of pyrolysis products, promoting the orderly growth of aromatic structures.
[0130] According to the present invention, in some embodiments, the volume ratio of reducing gas to oxygen in the mixed gas is 1.5-4:1, for example, 1.5:1, 2:1, 3:1, 4:1, or any range of two of the above ratios.
[0131] According to the present invention, in a mixture of reducing gas and oxygen, during the carbonization process, the carbonyl and phenolic hydroxyl groups in the bamboo-based carbon material can be reduced and oxidized to hydroxyl and quinone groups. The type of reducing gas can be selected from a wide range, and in some embodiments, the reducing gas includes hydrogen.
[0132] According to the present invention, in some embodiments, the nickel-based ternary material includes nickel-cobalt-manganese ternary cathode active material (NCM, LiNi). x Co y Mn z O2, where x > 0, y > 0, z > 0) and / or nickel-cobalt-aluminum ternary cathode active material (NCA, LiNi) x Co y Al z O2, where x > 0, y > 0, z > 0).
[0133] According to the present invention, the bamboo-based precursor refers to an intermediate product prepared from bamboo or its derivatives through physical, chemical, or biological methods, which can be used to synthesize high-performance materials (such as carbon materials, composite materials, etc.). In some embodiments, the method for obtaining the bamboo-based precursor includes: fully contacting an alkali metal aqueous solution with bamboo at a weight ratio of (7-9):(3-1) to ensure uniform reaction. The stirring speed is generally controlled at 200-500 r / min, and stirring is carried out for 4-6 hours. During the solution soaking process, mechanical stirring can promote the rapid diffusion of hydroxide ions in the solution into the interior of the bamboo, thereby improving the reaction efficiency. Finally, the stirred material is filtered, dried, and pulverized into precursor powder to facilitate uniform heating and carbonization. The alkali metal aqueous solution includes at least one of potassium hydroxide aqueous solution, sodium hydroxide aqueous solution, and lithium hydroxide aqueous solution. Sodium hydroxide aqueous solution is preferred because it has moderate reactivity when reacting with components such as cellulose and hemicellulose in bamboo, and can fully react with hemicellulose in bamboo, but will not cause excessive damage to the material structure like some more reactive alkali metal hydroxides.
[0134] According to the present invention, in some embodiments, the bamboo-based precursor is derived from at least one of moso bamboo, bitter bamboo, moso bamboo and kink bamboo.
[0135] According to the present invention, in some embodiments, the bamboo-based precursor is derived from moso bamboo.
[0136] The inventors of this invention discovered in their research that composite cathode materials prepared using bamboo-based precursors derived from moso bamboo exhibit better electrochemical performance. This is attributed to the ideal content of cellulose, hemicellulose, and lignin in the chemical composition of moso bamboo. The relatively high cellulose content allows for more efficient condensation and aromatization of small organic molecules generated during carbonization, resulting in high-quality bamboo-based carbon. Further research indicates that the cellulose content in moso bamboo can reach 40%-60%, higher than some other bamboo species. This abundant cellulose provides a sufficient raw material basis for forming bamboo carbon rich in aromatic groups, facilitating the subsequent formation of a core-shell structure with ternary materials and improving the material's conductivity, structural stability, and other properties. Furthermore, moso bamboo possesses a unique fiber structure with tightly packed and regular fiber bundles. During carbonization, this structure guides the directional arrangement of pyrolysis products, contributing to the formation of an ordered pore structure. The prepared bamboo carbon often exhibits higher porosity and a more reasonable pore size distribution, which is beneficial for sufficient contact between the electrolyte and the electrode material, promoting the transport of active ions (such as lithium ions). Compared to other types of bamboo, the bamboo-based carbon material formed from moso bamboo performs better in improving the overall performance of composite cathode materials.
[0137] According to the present invention, as long as the purpose of the present invention can be achieved, the solvent can be a conventional solvent in the art. In some embodiments, the solvent includes alcohol solvents, and the alcohol solvents that can be listed include at least one of methanol, ethanol and ethylene glycol.
[0138] The amount of ester compound used in step S1 of the present invention can be selected within a wide range. In some embodiments, the mass ratio of ester compound to bamboo-based precursor in step S1 is 1:0.8-2.5, for example, 1:0.8, 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2, 1:2.5, or any two of the above ratios, preferably 1:1-1.5.
[0139] In this invention, controlling the amount of ester compounds within the above-mentioned range can better promote the orderly growth of aromatic structures, and the resulting composite cathode material has better electrochemical performance.
[0140] According to the present invention, in some embodiments, in step S2, the mass of bamboo-based carbon is 1%-15% of the mass of the ternary material, for example, 1%, 2%, 4%, 6%, 8%, 10%, 12%, 15%, or any two of the above values, preferably 2%-5%.
[0141] The amount of alcohol solvent used in step S2 of this invention is not particularly limited, as long as it can achieve uniform mixing of bamboo-based carbon and nickel-based ternary materials. For example, the total mass of bamboo-based carbon and nickel-based ternary materials: volume of alcohol solvent = 100g: (5-15)mL.
[0142] As an example, step S1 includes: placing the bamboo-based precursor under a hydrogen-oxygen mixed gas with a volume ratio of 1.5-4:1, setting the pressure to 0.05-0.2 MPa, adding 0.8-2.5 times the mass of the bamboo-based precursor as a protective agent, heating from room temperature to 200-350°C at a rate of 1-5°C / min, holding at this temperature for 3-6 hours to carbonize the bamboo-based precursor and retain the aromatic groups in the precursor, and then cooling to room temperature to obtain bamboo-based carbon.
[0143] As an example, step S2 includes: mixing the bamboo-based carbon and nickel-based ternary material from step S1 in a mass ratio of (2-5):(95-98) in 5-15 mL of alcohol solvent, stirring for 2-5 h, filtering and drying, and then carbonizing and coating at 250-400 °C for 3-6 h to prepare a composite cathode material.
[0144] According to the present invention, the composite cathode material of the present invention can be used in cathode sheets. In some embodiments, a cathode sheet is provided, which includes a current collector, at least one side of the current collector is provided with a first active material layer, and a second active material layer is provided on the surface of the first active material layer away from the current collector; wherein the first active material layer and the second active material layer each independently contain the composite cathode material described above or the composite cathode material prepared by the preparation method described above.
[0145] The cathode sheet containing the composite cathode material of this invention has excellent electrochemical performance.
[0146] According to some embodiments of the present invention, the average thickness of the shell of the composite positive electrode material in the first active material layer is denoted as T1, and the average thickness of the shell of the composite positive electrode material in the second active material layer is denoted as T2, wherein T1 and T2 satisfy the following condition: T1 is greater than T2.
[0147] Based on the research on composite cathode materials of this invention, the inventors further discovered that the average thickness of the outer shell of the composite cathode material in the first active material layer is greater than that in the second active material layer. In other words, the mass percentage of the composite cathode material containing bamboo-based carbon material in the first active material layer is greater than that in the second active material layer. This results in a larger particle size of the composite cathode material in the first active material layer compared to the second active material layer. The first active material layer, primarily loaded with bamboo-based carbon material, contains a higher proportion of the ternary material, resulting in lower porosity in the outer shell. The thicker first active material layer (with a relatively high coating content) exhibits better conductivity and structural continuity. Once active ions, such as lithium ions, are captured by the second active material layer, the first active material layer, with its excellent electron transport capability, can rapidly conduct these ions to the coated material matrix. Due to the sufficient bamboo-based carbon material content in the first active material layer, a continuous and efficient ion transport channel is formed, reducing resistance during ion transport. During battery discharge, active ions, such as lithium ions, can be smoothly transported from the interior of the material through the bamboo-based carbon material in the first active material layer to the second active material layer, and then released into the electrolyte, effectively improving the battery's charge and discharge rate; the bamboo-based carbon material in the second active material layer has less coating on the ternary material. When bamboo-based carbon material is coated on ternary materials (such as LiNi...) x Co y Mn z When the O2 surface is exposed, the thinner outer shell (with a relatively low coating content) has a larger specific surface area. This allows the second active material layer to make full contact with the electrolyte, enabling it to quickly capture active ions (such as lithium ions) in the electrolyte during battery charging.
[0148] According to the present invention, in some embodiments, the numerical difference between T1 and T2 is 5-40nm, for example, 5nm, 10nm, 12.5nm, 15nm, 17.5nm, 20nm, 25nm, 30nm, 40nm, or any two of the above values, preferably 10-30nm.
[0149] According to the present invention, in some embodiments, the value of T1 is 15-50nm, for example, 15nm, 20nm, 22.5nm, 25nm, 27.5nm, 30nm, 40nm, 42.5nm, 50nm, or any range of two of the above values.
[0150] According to the present invention, in some embodiments, the value of T2 is 10-30nm, for example, 10nm, 15nm, 20nm, 22.5nm, 25nm, 27.5nm, 30nm, or any range of two of the above values.
[0151] According to the present invention, in some embodiments, the shell thickness of the composite cathode material in the first active material layer (15-50 nm) is greater than the shell thickness of the composite cathode material in the second active material layer (10-30 nm), that is, the mass percentage of the shell in the first active material layer to the composite cathode material is greater than the mass percentage of the shell in the second active material layer to the composite cathode material, thereby making the particle size of the composite cathode material in the first active material layer (160-300 nm) greater than the particle size of the composite cathode material in the second active material layer (150-260 nm).
[0152] According to some embodiments of the present invention, the thickness of the first active material layer and the thickness of the second active material layer are each independently 100 μm-150 μm.
[0153] According to the present invention, there are no special limitations on the specific type of current collector, as long as the purpose of the present invention can be achieved. It can refer to the metal materials commonly used in the art, such as including but not limited to platinum, palladium, aluminum, copper foil, etc.
[0154] According to the present invention, in order to enable the composite cathode material to better form the corresponding first active material layer and second active material layer, in some embodiments, the first active material layer and the second active material layer each independently contain a conductive agent and a binder.
[0155] According to the present invention, there is no particular limitation on the types of conductive agents and binders mentioned above, and each can be a type conventional in the art. For example, conductive agents include, but are not limited to, acetylene black, conductive carbon black, carbon nanotubes, carbon fibers and graphene, and binders include, but are not limited to, PVDF (polyvinylidene fluoride), polytetrafluoroethylene (PTFE) and styrene-butadiene rubber (SBR).
[0156] According to the present invention, in some embodiments, the mass content of the composite cathode material in the first active material layer and the second active material layer is each independently greater than 80%, preferably 81%-97%.
[0157] According to the present invention, the contents of the conductive agent and the binder can be selected within a wide range. For example, the mass content of the conductive agent in the first active material layer and the second active material layer is independently 2%-8%; for example, the mass content of the binder in the first active material layer and the second active material layer is independently 3%-10%.
[0158] According to the present invention, the preparation method of the above-mentioned positive electrode sheet is not particularly limited. As long as the purpose of the present invention can be achieved, it can be carried out according to the conventional preparation method in the art. Generally, a first active slurry providing a first active material layer and a second active slurry providing a second active material layer can be prepared first. That is, the respective positive electrode composite material, conductive agent and binder are dispersed in a solvent (e.g., N-methylpyrrolidone) to obtain the corresponding materials. Then, the slurry is coated onto the current collector in sequence, and then the positive electrode sheet is finally obtained after processes such as drying and rolling.
[0159] According to some embodiments of the present invention, the present invention provides a battery comprising a negative electrode and a positive electrode as described above.
[0160] The battery comprising the aforementioned positive electrode of the present invention exhibits excellent rate performance and cycle performance.
[0161] The specific type of battery used in this invention can be selected from a wide range, such as a lithium-ion battery. The lithium-ion battery is used as an example to illustrate the advantages of this invention, but it does not represent a limitation of this invention.
[0162] According to the present invention, those skilled in the art can select appropriate negative electrode sheets as needed. In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode active material layer includes a negative electrode material. In the present invention, there are no special limitations on the specific materials and structures of the negative electrode current collector and the negative electrode active material layer in the negative electrode sheet. Those skilled in the art can select specific materials and structures of the negative electrode current collector and the negative electrode active material layer that are known in the art as needed.
[0163] According to the present invention, in some embodiments, the battery further includes an electrolyte and a separator.
[0164] According to the present invention, there is no particular limitation on the specific type of electrolyte. All electrolytes suitable for lithium batteries in the art are applicable to the present invention, and the present invention will not elaborate further on them.
[0165] According to the present invention, the above-mentioned separator is known to those skilled in the art to be a variety of separators suitable for use in batteries, especially lithium-ion batteries, such as PP base film, PE base film, glass fiber mat or ultrafine glass fiber paper, etc.
[0166] According to the present invention, the battery described above can be assembled according to methods well known to those skilled in the art, such as winding the positive electrode, negative electrode and separator together, hot pressing, encapsulating, drying and then injecting electrolyte; and then aging and other steps to obtain the battery.
[0167] Example
[0168] The present invention will be described in more detail below by way of examples. The present invention is not limited to the following examples, and appropriate modifications can be made within the scope of the preceding and following text, all of which are included within the technical scope of the present invention. In the following examples, unless specific techniques or conditions are specified, they are performed according to the techniques or conditions described in the literature in the art or product instructions. All reagents, materials, or items whose manufacturers are not specified are conventional products that can be obtained commercially.
[0169] In the following examples and comparative examples:
[0170] Preparation of precursor bamboo powder: The bamboo was washed to remove surface impurities. The bamboo was stirred at a stirring speed of 400 r / min with a mass ratio of 8:1 and a 5% sodium hydroxide aqueous solution for 5 h. After stirring, the mixture was filtered, dried and pulverized to obtain precursor bamboo powder.
[0171] Preparation of precursor bitter bamboo powder: After removing surface impurities, bitter bamboo was stirred at a stirring speed of 400 r / min with a mass ratio of 8:1 and a 5% sodium hydroxide aqueous solution for 5 h. After stirring, the mixture was filtered, dried and pulverized to obtain precursor bitter bamboo powder.
[0172] Specific surface area determination: Surface impurities and moisture were removed from the prepared composite cathode material powder. The sample was then placed in an adsorption apparatus, and nitrogen gas was introduced at low temperature to measure the specific surface area of the material.
[0173] Conductivity determination: The prepared composite cathode material is pressed into a block and connected to a two-electrode tester, ensuring good contact between the electrodes and the sample. A certain voltage is applied, and the current passing through the sample is measured to obtain the conductivity.
[0174] Porosity determination: First, the sample is pretreated to remove surface impurities and moisture. Then, the sample is placed in an adsorption apparatus, and nitrogen gas is introduced at low temperature (such as liquid nitrogen temperature). The adsorption and desorption amounts of nitrogen are measured at different pressures to obtain the specific surface area of the sample. The porosity is then calculated by combining this with the density of the material.
[0175] The contents of aromatic groups, hydroxyl groups and quinone groups were determined by GC-MS.
[0176] Example 1
[0177] 1. Preparation of composite cathode material A1:
[0178] Preparation of S1 bamboo-based carbon A1: 5g of precursor bamboo powder was placed in a hydrogen-oxygen mixed gas with a volume ratio of 2:1 and the pressure was set to 0.1 MPa. 3mL of trimethyl phosphate was added as a protective reagent. The temperature was increased from room temperature to 275℃ at a rate of 3℃ / min and held for 3h to carbonize the precursor powder and retain the aromatic groups in the precursor. Then it was cooled to room temperature to obtain bamboo-based carbon A1.
[0179] S2 mixes the above-mentioned bamboo-based carbon A1 with ternary cathode material NCM523 in 10 mL of ethanol solvent at a mass ratio of 3:97. After mixing and stirring for 3 h, the mixture is filtered and dried, and then carbonized and coated at 325 °C for 4 h to prepare composite cathode material A1.
[0180] SEM image of composite cathode material A1 is shown below Figure 1 As shown, the composite cathode material A1 has a core-shell structure with an average particle size of 225 nm, an average particle size of NCM523 core of 150 nm, and an average thickness of 75 nm, which is twice the average thickness of the bamboo-based carbon material shell.
[0181] The infrared spectrum of the bamboo-based carbon material shell of composite cathode material A1 is shown below. Figure 2 As shown.
[0182] 2. Preparation of composite cathode material A2:
[0183] Preparation of S1 bamboo-based carbon A2: Same as preparation of bamboo-based carbon A1.
[0184] S2 mixes the above-mentioned bamboo-based carbon A2 with ternary cathode material NCM523 in 10 mL of ethanol solvent at a mass ratio of 3:97. After mixing and stirring for 3 h, the mixture is filtered and dried, and then carbonized and coated at 300 °C for 3.5 h to prepare composite cathode material A2.
[0185] The composite cathode material A2 has a core-shell structure with an average particle size of 190 nm. The core NCM523 has an average particle size of 150 nm, and the outer shell bamboo-based carbon material has an average thickness of 40 nm, which is twice the average thickness of the core.
[0186] 3. Preparation of positive electrode sheet:
[0187] Composite cathode material A1 and composite cathode material A2 are mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 85:7:8, respectively. Then, N-methylpyrrolidone is added and stirred to make the mass content of the slurry 62% to obtain the corresponding cathode slurry A1 and cathode slurry A2. Cathode slurry A1 and cathode slurry A2 are then uniformly coated on aluminum foil current collector to form a first active material layer with a thickness of 110 μm and a second active material layer with a thickness of 120 μm to obtain the cathode sheet.
[0188] Example 2
[0189] 1. Preparation of composite cathode material B1:
[0190] Preparation of S1 bamboo-based carbon B1: 4g of precursor bamboo powder was placed in a hydrogen-oxygen mixed gas with a volume ratio of 2:1 and the pressure was set to 0.05 MPa. 2mL of trimethyl phosphate was added as a protective reagent. The temperature was increased from room temperature to 200℃ at a rate of 1℃ / min and held for 2h to carbonize the precursor powder and retain the aromatic groups in the precursor. Then it was cooled to room temperature to obtain bamboo-based carbon B1.
[0191] S2 mixes the above-mentioned bamboo-based carbon B1 with ternary cathode material NCM523 in 5 mL of ethanol solvent at a mass ratio of 2:98. After mixing and stirring for 2 h, the mixture is filtered and dried, and then carbonized and coated at 250 °C for 3.6 h to prepare composite cathode active material B1.
[0192] The composite positive electrode active material B1 has a core-shell structure with an average particle size of 205 nm. The core NCM523 has an average particle size of 150 nm, and the outer shell is twice the average thickness of the bamboo-based carbon material, which is 55 nm.
[0193] 2. Preparation of composite cathode material B2:
[0194] Preparation of S1 bamboo-based carbon B2: Same as the preparation of bamboo-based carbon A1 in Example 1.
[0195] S2 mixes the above-mentioned bamboo-based carbon B2 with ternary cathode material NCM523 in 10 mL of ethanol solvent at a mass ratio of 2:98. After mixing and stirring for 3 h, the mixture is filtered, dried, and then carbonized and coated at 300 °C for 3.2 h to prepare composite cathode material B2.
[0196] The composite cathode material B2 has a core-shell structure with an average particle size of 180 nm. The core NCM523 has an average particle size of 150 nm, and the outer shell bamboo-based carbon material has an average thickness of 30 nm, which is twice the average thickness.
[0197] 3. Preparation of the positive electrode:
[0198] Composite cathode material B1 and composite cathode material B2 were mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 85:7:8, respectively. Then, N-methylpyrrolidone was added and stirred to make the mass content of the slurry 62% to obtain the corresponding cathode slurry B1 and cathode slurry B2. Cathode slurry B1 and cathode slurry B2 were then uniformly coated on aluminum foil current collector to form a first active material layer with a thickness of 110 μm and a second active material layer with a thickness of 120 μm to obtain the cathode sheet.
[0199] Example 3
[0200] 1. Preparation of composite cathode material C1:
[0201] Preparation of S1 bamboo-based carbon C1: 6g of precursor bamboo powder was placed in a hydrogen-oxygen mixed gas with a volume ratio of 2:1 and the pressure was set to 0.2 MPa. 4mL of trimethyl phosphate was added as a protective reagent. The temperature was increased from room temperature to 350℃ at a rate of 5℃ / min and held for 4h to carbonize the precursor powder and retain the aromatic groups in the precursor. Then it was cooled to room temperature to obtain bamboo-based carbon C1.
[0202] S2 mixes the above-mentioned bamboo-based carbon C1 with ternary cathode material NCM523 in 15 mL of ethanol solvent at a mass ratio of 4:96. After mixing and stirring for 4 h, the mixture is filtered and dried, and then carbonized and coated at 400 °C for 4.5 h to prepare composite cathode material C1.
[0203] The composite cathode material C1 has a core-shell structure with an average particle size of 235 nm. The core NCM523 has an average particle size of 150 nm, and the outer shell is twice the average thickness of the bamboo-based carbon material, which is 85 nm.
[0204] 2. Preparation of composite cathode material B2:
[0205] Preparation of S1 bamboo-based carbon B2: Same as the preparation of bamboo-based carbon A1 in Example 1.
[0206] S2 mixes the above-mentioned bamboo-based carbon C2 with ternary cathode material NCM523 in 10 mL of ethanol solvent at a mass ratio of 2:98. After mixing and stirring for 3 h, the mixture is filtered and dried, and then carbonized and coated at 300 °C for 3.55 h to prepare composite cathode material C2.
[0207] The composite cathode material C2 has a core-shell structure with an average particle size of 195 nm. The core NCM523 has an average particle size of 150 nm, and the outer shell bamboo-based carbon material has an average thickness of 45 nm, which is twice the average thickness.
[0208] 3. Preparation of the positive electrode:
[0209] Composite cathode material C1 and composite cathode material C2 are mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 85:7:8, respectively. Then, an appropriate amount of N-methylpyrrolidone is added and stirred to make the mass content of the slurry 62% to obtain the corresponding cathode slurry C1 and cathode slurry C2. Cathode slurry C1 and cathode slurry C2 are then uniformly coated on aluminum foil current collector to form a first active material layer with a thickness of 110 μm and a second active material layer with a thickness of 120 μm to obtain the cathode sheet.
[0210] Example 4
[0211] The method of Example 1 is the same, except that the precursor bamboo powder is replaced with the precursor bitter bamboo powder.
[0212] The final prepared composite cathode material D1, composite cathode material D2, and cathode sheet were obtained.
[0213] Among them, the composite cathode material D1 has a core-shell structure with an average particle size of 225nm, an average particle size of NCM523 core of 150nm, and a shell of bamboo-based carbon material with an average thickness of 75nm, which is twice the average thickness.
[0214] The infrared spectrum of the bamboo-based carbon material shell of composite cathode material D1 is shown below. Figure 3 As shown.
[0215] The composite cathode material D2 has a core-shell structure with an average particle size of 190 nm. The core NCM523 has an average particle size of 150 nm, and the outer shell is twice the average thickness of the bamboo-based carbon material, which is 40 nm.
[0216] Example 5
[0217] The method of Example 1 was followed, except that trimethyl phosphate was replaced with trimethyl borate, and composite cathode material E1, composite cathode material E2, and cathode sheet were finally prepared.
[0218] Among them, the composite cathode material E1 has a core-shell structure with an average particle size of 225nm, an average particle size of NCM523 core of 150nm, and a shell of bamboo-based carbon material with an average thickness of 75nm, which is twice the average thickness.
[0219] The composite cathode material E2 has a core-shell structure with an average particle size of 190 nm. The core NCM523 has an average particle size of 150 nm, and the outer shell is twice the average thickness of the bamboo-based carbon material, which is 40 nm.
[0220] Example 6
[0221] 1. Preparation of composite cathode material F1:
[0222] Preparation of S1 bamboo-based carbon F1: 5g of precursor bamboo powder was placed in a hydrogen-oxygen mixed gas with a volume ratio of 2:1 and the pressure was set to 0.1 MPa. 3mL of trimethyl phosphate was added as a protective reagent. The temperature was increased from room temperature to 275℃ at a rate of 3℃ / min and held for 3h to carbonize the precursor powder and retain the aromatic groups in the precursor. Then it was cooled to room temperature to obtain bamboo-based carbon F1.
[0223] S2 mixes the above-mentioned bamboo-based carbon F1 with ternary cathode material NCM523 in 10 mL of ethanol solvent at a mass ratio of 3:97. After mixing and stirring for 3 h, the mixture is filtered and dried. Then, it is carbonized and coated at 325 °C for 3.58 h to prepare composite cathode material F1.
[0224] The composite cathode material F1 has a core-shell structure with an average particle size of 200 nm. The core NCM523 has an average particle size of 150 nm, and the outer shell is twice the average thickness of the bamboo-based carbon material, which is 50 nm.
[0225] 2. Preparation of composite cathode material F2:
[0226] Preparation of S1 bamboo-based carbon F2: Same as preparation of bamboo-based carbon F1.
[0227] S2 mixes the above-mentioned bamboo-based carbon F2 with ternary cathode material NCM523 in 10 mL of ethanol solvent at a mass ratio of 2:98. After mixing and stirring for 3 h, the mixture is filtered and dried, and then carbonized and coated at 300 °C for 3.25 h to prepare composite cathode material F2.
[0228] The composite cathode material F2 has a core-shell structure with an average particle size of 185 nm. The core NCM523 has an average particle size of 150 nm, and the outer shell is twice the average thickness of the bamboo-based carbon material, which is 35 nm.
[0229] 3. Preparation of positive electrode sheet:
[0230] Composite cathode material F1 and composite cathode material F2 were mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 85:7:8, respectively. Then, N-methylpyrrolidone was added and stirred to make the mass content of the slurry 62% to obtain the corresponding cathode slurry F1 and cathode slurry F2. Cathode slurry F1 and cathode slurry F2 were then uniformly coated on aluminum foil current collector to form a first active material layer with a thickness of 110 μm and a second active material layer with a thickness of 120 μm to obtain the cathode sheet.
[0231] Example 7
[0232] 1. Preparation of composite cathode material G1:
[0233] Preparation of S1 bamboo-based carbon G1: 5g of precursor bamboo powder was placed in a hydrogen-oxygen mixed gas with a volume ratio of 2:1 and the pressure was set to 0.1 MPa. 3mL of trimethyl phosphate was added as a protective reagent. The temperature was increased from room temperature to 275℃ at a rate of 3℃ / min and held for 3h to carbonize the precursor powder and retain the aromatic groups in the precursor. Then it was cooled to room temperature to obtain bamboo-based carbon G1.
[0234] S2 mixes the above-mentioned bamboo-based carbon G1 with ternary cathode material NCM523 in 10 mL of ethanol solvent at a mass ratio of 3:97. After mixing and stirring for 3 h, the mixture is filtered and dried. Then, it is carbonized and coated at 325 °C for 5 h to prepare composite cathode material G1.
[0235] The composite cathode material G1 has a core-shell structure with an average particle size of 250 nm. The core NCM523 has an average particle size of 150 nm, and the outer shell is twice the average thickness of the bamboo-based carbon material, which is 100 nm.
[0236] 2. Preparation of composite cathode material G2:
[0237] Preparation of S1 bamboo-based carbon G2: Same as preparation of bamboo-based carbon G1.
[0238] S2 mixes the above-mentioned bamboo-based G2 with the ternary cathode material NCM523 in 10 mL of ethanol solvent at a mass ratio of 4:96. After mixing and stirring for 3 h, the mixture is filtered and dried, and then carbonized and coated at 300 °C for 3.58 h to prepare the composite cathode material G2.
[0239] The composite cathode material G2 has a core-shell structure with an average particle size of 200 nm. The core NCM523 has an average particle size of 150 nm, and the outer shell is twice the average thickness of the bamboo-based carbon material, which is 50 nm.
[0240] 3. Preparation of positive electrode sheet:
[0241] Composite cathode material G1 and composite cathode material G2 are mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 85:7:8, respectively. Then, N-methylpyrrolidone is added and stirred to make the mass content of the slurry 62% to obtain the corresponding cathode slurry G1 and cathode slurry G2. Cathode slurry G1 and cathode slurry G2 are then uniformly coated on aluminum foil current collector to form a first active material layer with a thickness of 110 μm and a second active material layer with a thickness of 120 μm to obtain the cathode sheet.
[0242] Example 8
[0243] 1. Preparation of composite cathode material H1: Same as the preparation of composite cathode material F1 in Example 6;
[0244] 2. Preparation of composite cathode material H2: Same as the preparation of composite cathode material G2 in Example 7;
[0245] 3. Preparation of positive electrode sheet: Composite positive electrode material H1 and composite positive electrode material H2 are mixed with acetylene black and polyvinylidene fluoride at a mass ratio of 85:7:8, respectively. Then, N-methylpyrrolidone is added and stirred to make the mass content of the slurry 62% to obtain the corresponding positive electrode slurry H1 and positive electrode slurry H2. Positive electrode slurry H1 and positive electrode slurry H2 are uniformly coated on aluminum foil current collector to form a first active material layer with a thickness of 110μm and a second active material layer with a thickness of 120μm to obtain the positive electrode sheet.
[0246] Example 9
[0247] 1. Preparation of composite cathode material I1:
[0248] Preparation of S1 bamboo-based carbon I1: 5g of precursor bamboo powder was placed in a hydrogen-oxygen mixed gas with a volume ratio of 2:1 and the pressure was set to 0.1 MPa. 3mL of trimethyl phosphate was added as a protective reagent. The temperature was increased from room temperature to 500℃ at a rate of 3℃ / min and held for 3h to carbonize the precursor powder and retain the aromatic groups in the precursor. Then it was cooled to room temperature to obtain bamboo-based carbon I1.
[0249] S2 mixes the above-mentioned bamboo-based carbon I1 with ternary cathode material NCM523 in 10 mL of ethanol solvent at a mass ratio of 3:97. After mixing and stirring for 3 h, the mixture is filtered and dried, and then carbonized and coated at 550 °C for 4.2 h to prepare composite cathode material I1.
[0250] The composite cathode material I1 has a core-shell structure with an average particle size of 230 nm. The core NCM523 has an average particle size of 150 nm, and the outer shell is twice the average thickness of the bamboo-based carbon material, which is 80 nm.
[0251] 2. Preparation of composite cathode material I2:
[0252] Preparation of S1 bamboo-based carbon I2: Same as preparation of bamboo-based carbon I1.
[0253] S2 mixes the above-mentioned bamboo-based carbon I2 with ternary cathode material NCM523 in 10 mL of ethanol solvent at a mass ratio of 3:97. After mixing and stirring for 3 h, the mixture is filtered and dried, and then carbonized and coated at 300 °C for 3.55 h to prepare composite cathode material I2.
[0254] The composite cathode material I2 has a core-shell structure with an average particle size of 195 nm. The core NCM523 has an average particle size of 150 nm, and the outer shell bamboo-based carbon material has an average thickness of 45 nm, which is twice the average thickness of the core.
[0255] 3. Preparation of positive electrode sheet:
[0256] Composite cathode material I1 and composite cathode material I2 were mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 85:7:8, respectively. Then, N-methylpyrrolidone was added and stirred to make the mass content of the slurry 62% to obtain the corresponding cathode slurry I1 and cathode slurry I2. Cathode slurry I1 and cathode slurry I2 were then uniformly coated on aluminum foil current collector to form a first active material layer with a thickness of 110 μm and a second active material layer with a thickness of 120 μm to obtain the cathode sheet.
[0257] Example 10
[0258] 1. Preparation of composite cathode material J1: Same as the preparation of composite cathode material A1 in Example 1.
[0259] 2. Preparation of composite cathode material J2: Same as the preparation of composite cathode material A2 in Example 1.
[0260] Composite cathode material J1 and composite cathode material J2 are mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 85:7:8, respectively. Then, N-methylpyrrolidone is added and stirred to make the mass content of the slurry 62% to obtain the corresponding cathode slurry J1 and cathode slurry J2. Cathode slurry J2 and cathode slurry J1 are then uniformly coated on aluminum foil current collector to form a first active material layer with a thickness of 110 μm and a second active material layer with a thickness of 120 μm to obtain the cathode sheet.
[0261] Comparative Example 1
[0262] 1. Preparation of composite cathode material K:
[0263] Commercial carbon material (conductive carbon black Super P) and ternary cathode material NCM523 were mixed in 10 mL of ethanol solvent at a ratio of 3:97. After mixing and stirring for 3 h, the mixture was filtered and dried. Then, it was carbonized and coated at 325 °C for 4 h to prepare composite cathode material I.
[0264] The composite cathode material K has a core-shell structure with an average particle size of 225 nm. The core NCM523 has an average particle size of 150 nm, and the shell carbon material has an average thickness of 75 nm, which is twice the average thickness.
[0265] 2. Preparation of the positive electrode:
[0266] The composite cathode material K, acetylene black and polyvinylidene fluoride were mixed in a mass ratio of 85:7:8, and then N-methylpyrrolidone was added and stirred to make the mass content of the slurry 62%. The cathode slurry was prepared by stirring and uniformly coating the cathode slurry onto an aluminum foil current collector to form an active material layer with a thickness of 230 μm to obtain the cathode sheet.
[0267] Comparative Example 2
[0268] 1. Preparation of composite cathode material L1:
[0269] Preparation of S1 bamboo-based carbon L1: 5g of precursor bamboo powder was placed under nitrogen gas at a pressure of 0.1 MPa. 3mL of trimethyl phosphate was added as a protective agent. The temperature was increased from room temperature to 275℃ at a rate of 3℃ / min and held for 3h to carbonize the precursor powder and retain the aromatic groups in the precursor. Then it was cooled to room temperature to obtain bamboo-based carbon L1.
[0270] S2 mixes the above-mentioned bamboo-based carbon L1 with ternary cathode material NCM523 in 10 mL of ethanol solvent at a mass ratio of 3:97. After mixing and stirring for 3 h, the mixture is filtered and dried, and then carbonized and coated at 325 °C for 4 h to prepare composite cathode material L1.
[0271] The composite cathode material L1 has a core-shell structure with an average particle size of 225 nm. The core NCM523 has an average particle size of 150 nm, and the outer shell is twice the average thickness of the bamboo-based carbon material, which is 75 nm.
[0272] 2. Preparation of composite cathode material L2:
[0273] Preparation of S1 bamboo-based carbon L2: Same as preparation of bamboo-based carbon L1.
[0274] S2 mixes the above-mentioned bamboo-based carbon L2 with ternary cathode material NCM523 in 10 mL of ethanol solvent at a mass ratio of 3:97. After mixing and stirring for 3 h, the mixture is filtered and dried, and then carbonized and coated at 300 °C for 3.5 h to prepare composite cathode material L2.
[0275] The composite cathode material L2 has a core-shell structure with an average particle size of 190 nm. The core NCM523 has an average particle size of 150 nm, and the outer shell is twice the average thickness of the bamboo-based carbon material, which is 40 nm.
[0276] 3. Preparation of positive electrode sheet:
[0277] Composite cathode material L1 and composite cathode material L2 were mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 85:7:8, respectively. Then, N-methylpyrrolidone was added and stirred to make the mass content of the slurry 62% to obtain the corresponding cathode slurry L1 and cathode slurry L2. Cathode slurry L1 and cathode slurry L2 were then uniformly coated on aluminum foil current collector to form a first active material layer with a thickness of 110 μm and a second active material layer with a thickness of 120 μm to obtain the cathode sheet.
[0278] Comparative Example 3
[0279] 1. Preparation of composite cathode material M1:
[0280] Preparation of S1 bamboo-based carbon M1: 5g of precursor bamboo powder was placed in a hydrogen-oxygen mixed gas with a volume ratio of 2:1 and the pressure was set to 0.1 MPa. The temperature was increased from room temperature to 275℃ at a rate of 3℃ / min and held for 3h to carbonize the precursor powder and retain the aromatic groups in the precursor. Then it was cooled to room temperature to obtain bamboo-based carbon M1.
[0281] S2 mixes the above-mentioned bamboo-based carbon M1 with ternary cathode material NCM523 in 10 mL of ethanol solvent at a mass ratio of 3:97. After mixing and stirring for 3 h, the mixture is filtered and dried. Then, it is carbonized and coated at 325 °C for 4 h to prepare composite cathode material M1.
[0282] The composite cathode material M1 has a core-shell structure with an average particle size of 225 nm. The core NCM523 has an average particle size of 150 nm, and the outer shell is twice the average thickness of the bamboo-based carbon material, which is 75 nm.
[0283] 2. Preparation of composite cathode material M2:
[0284] Preparation of S1 bamboo-based carbon M2: Same as preparation of bamboo-based carbon M1.
[0285] S2 mixes the above-mentioned bamboo-based carbon M2 with ternary cathode material NCM523 in 10 mL of ethanol solvent at a mass ratio of 3:97. After mixing and stirring for 3 h, the mixture is filtered and dried, and then carbonized and coated at 300 °C for 3.5 h to prepare composite cathode material M2.
[0286] The composite cathode material M2 has a core-shell structure with an average particle size of 190 nm. The core NCM523 has an average particle size of 150 nm, and the outer shell bamboo-based carbon material has an average thickness of 40 nm, which is twice the average thickness.
[0287] 3. Preparation of positive electrode sheet:
[0288] Composite cathode material M1 and composite cathode material M2 are mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 85:7:8, respectively. Then, N-methylpyrrolidone is added and stirred to make the mass content of the slurry 62% to obtain the corresponding cathode slurry M1 and cathode slurry M2. Cathode slurry M1 and cathode slurry M2 are then uniformly coated on aluminum foil current collector to form a first active material layer with a thickness of 110 μm and a second active material layer with a thickness of 120 μm to obtain the cathode sheet.
[0289] The porosity, specific surface area, and mass content of aromatic groups, hydroxyl groups, and quinone groups in the shell of the composite cathode materials in Examples 1-7, Example 9, and Comparative Examples 1-3 were tested respectively. The test results are shown in Table 1.
[0290] Table 1
[0291]
[0292]
[0293] Performance testing
[0294] 1. Batteries were prepared by combining the positive and negative electrode sheets from Examples 1-10 and Comparative Examples 1-3, respectively.
[0295] The negative electrode sheet is prepared as follows: Graphite, acetylene black, binder PVDF5130 and thickener CMC MAC500 are mixed with deionized oil in a mass ratio of 96:2:1:1 to prepare a negative electrode slurry with a mass content of 62%. The negative electrode slurry is uniformly coated on a copper foil current collector, and the negative electrode sheet is obtained by cold pressing and slicing.
[0296] Battery preparation: The positive electrode, negative electrode and PE base film are wound together, hot-pressed, packaged and dried, then injected with commercial electrolyte, and then the battery is prepared by steps including aging.
[0297] 2. Test the batteries containing the positive electrode sheets from Examples 1-10 and Comparative Examples 1-3.
[0298] (1) Cyclic test: At 25±2℃, the battery was charged to 3.65V with constant current and constant voltage at 1C and cut off current of 0.05C; it was left to stand for 30min, and then discharged to 2.5V at 1C. The above process was continued, and the capacity C0 after the first charge was recorded. At the same time, the capacity C500 of the battery after 500 cycles was recorded. The capacity retention rate of the battery after 500 cycles was calculated as C500 / C0*100%.
[0299] (2) Initial Coulombic Efficiency Test: Charge the battery at 1C constant current and constant voltage to 3.65V, with a cutoff current of 0.05C; let it stand for 30 minutes, then discharge it at 1C to 2.5V to obtain the discharge capacity C0; then charge it at 1C constant current and constant voltage to 3.65V, with a cutoff current of 0.05C to obtain the charging capacity C1. Calculate the initial Coulombic Efficiency = C0 / C1*100%.
[0300] The test results are shown in Table 2 below.
[0301] Table 2
[0302]
[0303]
[0304] As can be seen from Tables 1 and 2, the composite cathode material in this invention has a core-shell structure, and the shell includes bamboo-based carbon material containing aromatic groups, which enables the battery made with the composite cathode material to have initial coulombic efficiency and cycle performance. The main reason for this is that the bamboo-based carbon material in this invention has a rich porous structure and specific surface area, which can promote the transport and diffusion of lithium ions and improve the charge and discharge performance of the battery. In addition, the bamboo-based carbon material with a framework structure constructed with aromatic groups can form a strong interaction with the core, enhance the interfacial bonding force between the two, make the structure of the composite cathode material more stable, and help maintain structural integrity during charge and discharge, thereby improving the cycle performance of the battery. At the same time, the aromatic groups have a conjugated π electron system, which enables the composite cathode material to maintain a high capacity. Compared with the core material alone, the capacity retention rate can be improved by 10-20%. In addition, the aromatic groups have certain chemical activity and can react with some components in the electrolyte to form a more stable and dense solid electrolyte interface (SEI) film on the surface of the composite cathode material. This SEI film can prevent the electrolyte from further reacting with the core, reduce the consumption of active lithium, and thus improve the coulombic efficiency of the battery.
[0305] The parts of this invention not described in detail are techniques known to those skilled in the art.
[0306] The basic principles of the present invention have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in the present invention are merely examples and not limitations, and should not be considered as essential features of each embodiment of the present invention. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the present invention to the necessity of employing the aforementioned specific details.
[0307] It should be noted that the terms "and / or" or " / " used herein are merely descriptions of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. The singular forms "a," "described," and "the" used in the embodiments of the invention and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.
[0308] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.
[0309] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a composite cathode material, characterized by, The preparation method includes: S1. In the presence of a mixed gas containing reducing gas and oxygen and ester compounds, the bamboo-based precursor is carbonized to obtain bamboo-based carbon, wherein the ester compounds include at least one of phosphate esters, borate esters and carboxylic esters. S2. The bamboo-based carbon and ternary material are mixed in the presence of a solvent, and then dried and carbonized to obtain the composite cathode material. The composite cathode material has a core-shell structure, including a core and a shell. The core comprises a ternary material, and the shell covers at least a portion of the core. The shell comprises a bamboo-based carbon material, and the bamboo-based carbon material contains aromatic groups. The carbonization temperature in step S1 and the carbonization coating temperature in step S2 are each independently 200-400℃.
2. The method for preparing the composite cathode material according to claim 1, characterized in that, The carbonization temperature in step S1 is lower than the carbonization coating temperature in step S2; and / or, In step S1, the carbonization conditions include: a pressure of 0.05-0.2 MPa, a temperature of 200-350°C, and a time of 2-5 hours; and / or, In step S2, the carbonization coating conditions include: a temperature of 250-400℃ and a time of 3-6 hours.
3. The method for preparing the composite cathode material according to claim 2, characterized in that, The temperature difference between carbonization in step S1 and carbonization coating in step S2 is 30-100℃.
4. The method for preparing the composite cathode material according to claim 1, characterized in that, The ester compounds include phosphate esters; and / or, In the mixture, the volume ratio of reducing gas to oxygen is 1.5-4:1; and / or, The reducing gas includes hydrogen; and / or, The ternary material includes nickel-based ternary materials; and / or, The bamboo-based precursor is derived from at least one of the following: *Phyllostachys pubescens*, *Phyllostachys aurea*, *Phyllostachys nigra*, and *Phyllostachys pubescens*; and / or, The solvent includes alcohol solvents; and / or, In step S1, the mass ratio of the ester compound to the bamboo-based precursor is 1:0.8-2.5; and / or, In step S2, the mass of the bamboo-based carbon is 1%-15% of the mass of the ternary material.
5. The method for preparing the composite cathode material according to claim 4, characterized in that, The phosphate ester includes at least one of trimethyl phosphate, triethyl phosphate, and tripropyl phosphate.
6. The method for preparing the composite cathode material according to claim 5, characterized in that, The phosphate ester is trimethyl phosphate.
7. The method for preparing the composite cathode material according to claim 4, characterized in that, The nickel-based ternary material includes nickel-cobalt-manganese ternary cathode active material and / or nickel-cobalt-aluminum ternary cathode active material.
8. The method for preparing the composite cathode material according to claim 4, characterized in that, The alcohol solvent includes at least one of methanol, ethanol, or ethylene glycol.
9. The method for preparing the composite cathode material according to claim 4, characterized in that, In step S1, the mass ratio of the ester compound to the bamboo-based precursor is 1:1-1.
5.
10. The method for preparing the composite cathode material according to claim 4, characterized in that, The mass of the bamboo-based carbon is 2%-5% of the mass of the ternary material.
11. A composite cathode material, characterized in that, The composite cathode material is prepared by the method described in any one of claims 1-10; The composite cathode material has a core-shell structure, including a core and a shell; The core comprises a ternary material, and the outer shell covers at least a portion of the core, the outer shell comprising a bamboo-based carbon material; The bamboo-based carbon material contains aromatic groups.
12. The composite cathode material according to claim 11, characterized in that, Based on the mass of the bamboo-based carbon material, the mass content of the aromatic groups is 12%-16%; and / or, The aromatic group includes phenyl; and / or, The bamboo-based carbon material also contains hydroxyl and / or quinone groups.
13. The composite cathode material according to claim 12, characterized in that, Based on the total mass of aromatic groups, the hydroxyl content is 8%-12% by mass; and / or, Based on the total mass of aromatic groups, the mass content of the quinone group is 10%-15%.
14. The composite cathode material according to any one of claims 11-13, characterized in that, The composite cathode material satisfies at least one of the following characteristics: (1) The porosity of the composite cathode material is 60%-80%; (2) The specific surface area of the composite cathode material is 200-1000 m² / g; (3) The conductivity of the composite cathode material is 10-100 S / cm; (4) The average particle size of the composite cathode material is 150nm-300nm; (5) The average particle size of the kernel is 130nm-200nm; (6) The average thickness of the outer shell is 10nm-50nm; (7) The ternary material includes nickel-based ternary materials.
15. The composite cathode material according to claim 14, characterized in that, The specific surface area of the composite cathode material is 700-950 m² / g.
16. The composite cathode material according to claim 14, characterized in that, The conductivity of the composite cathode material is 90-100 S / cm.
17. A positive electrode plate, characterized in that, The device includes a current collector, wherein at least one side of the current collector is provided with a first active material layer, and a second active material layer is provided on the surface of the first active material layer away from the current collector. The first active material layer and the second active material layer each independently contain the composite cathode material according to any one of claims 11-16.
18. The positive electrode sheet according to claim 17, characterized in that, The average thickness of the composite cathode material shell in the first active material layer is denoted as T1, and the average thickness of the composite cathode material shell in the second active material layer is denoted as T2. T1 and T2 satisfy the condition that T1 is greater than T2.
19. The positive electrode sheet according to claim 18, characterized in that, The numerical difference between T1 and T2 is 5nm-40nm; and / or, The T1 is 15nm-50nm; and / or, The T2 is 10nm-30nm.
20. The positive electrode sheet according to claim 19, characterized in that, The numerical difference between T1 and T2 is 10nm-30nm.
21. The positive electrode sheet according to claim 17, characterized in that, The thickness of the first active material layer and the thickness of the second active material layer are each independently 100 μm-150 μm; and / or, The first active material layer and the second active material layer each independently contain a conductive agent and a binder; and / or, The mass content of the composite cathode material in the first active material layer and the second active material layer is independently greater than 80%.
22. A battery, characterized in that, It includes the negative electrode and the positive electrode as described in any one of claims 17-21.
Citation Information
Patent Citations
Preparation method for novel lithium vanadium phosphate / bamboo charcoal composite cathode material
CN102332582A
Positive electrode material and preparation method and application thereof
CN114464800A
